The 340b Program, Contract Pharmacies, Hospitals, and Patients: An Evolving Relationship Impacting Health Care Delivery. Issue 4 (October 2019) - Ruley, Morgan; Belcher, Morgan; Sayre, Hannah; Coustasse, Alberto
Abstract : The 340B Drug Pricing Program, created by Congress in 1992 through the Veterans Health Care Act, has provided discounted drug prices to hospitals and other health care organizations serving a wide population of low-income patients. Some 340B programs use contract pharmacies, an arrangement whereby the hospital or health care organization signs a contract directly with a pharmacy to provide covered pharmacy services at discounted prices. The federal 340B Drug Pricing Program has provided access to reduced price prescription drugs to more than 35 000 individual health care facilities and sites certified by the US Department of Health and Human Services, and clinics have served more than 10 million people in all 50 states, plus commonwealths and US territories. The 340B program has increased profits for hospitals through contract pharmacies because they have still received the same reimbursement but acquired drugs at a lower rate.